1994
DOI: 10.1037/h0089243
|View full text |Cite
|
Sign up to set email alerts
|

Spousal adjustment to a postmarital disability in one partner.

Abstract: This article investigates spousal adjustment to a postmarital disability in one partner in relation to the personal, marital, and social aspects of the couple’s relationship. The study examines the differences between spousal adjustment to a spinal cord injury or a neurologically disabling condition of one partner, as well as the impact of gender on the situation. The study was based on a sample of 71 couples. The results revealed a positive correlation between the adjustment of both spouses to the disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(49 reference statements)
1
8
0
3
Order By: Relevance
“…Spouses have also reported that they have a stronger fear of separation and a higher sense of dependency as a result of SCI. 1,26,27 The spouses of SCI patients who in most cases are also the carers were reported to have much stress related to the injury in aspects of ®nancial, psychological, marital and social relationships. 9,11,13 Kreuter 28 reported that care giving often changes the balance of power in the marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Spouses have also reported that they have a stronger fear of separation and a higher sense of dependency as a result of SCI. 1,26,27 The spouses of SCI patients who in most cases are also the carers were reported to have much stress related to the injury in aspects of ®nancial, psychological, marital and social relationships. 9,11,13 Kreuter 28 reported that care giving often changes the balance of power in the marriage.…”
Section: Discussionmentioning
confidence: 99%
“…An illness at this stage of family lifecycle is often associated with feelings of failure, guilt towards children, fatigue and emotional burnout. The sixth stage in the family lifecycle involves focusing on health problems. The spouse may lack the emotional and physical strength to fight an illness at this stage of the couple's life [9,10]. If one of the children with chronic disease is still living with his/her parents, another solution may be warranted in order to take further care of the sick person.…”
Section: The Impact Of Illness Upon the Family's Lifecyclementioning
confidence: 99%
“…sex, job, or travelling), and how well the couple is able to balance the limitations of the illness and come to terms with it Strauss 1988, 1993). Studies indicate that spouses of persons with chronic illness tended to report higher rates of depression, greater use of psychotropic drugs, poorer self-reported health, more relinquished social activities, and an increased number of new roles and responsibilities (Gilliss 1991, Pruchno and Potashnik 1989, Manne and Zautra 1990, Feigin 1994.…”
Section: Introductionmentioning
confidence: 98%